2000
DOI: 10.1007/pl00000744
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the type 1 insulin-like growth factor receptor

Abstract: The type 1 insulin-like growth factor receptor (IGF-1R), a transmembrane tyrosine kinase, is widely expressed across many cell types in foetal and postnatal tissues. Activation of the receptor following binding of the secreted growth factor ligands IGF-1 and IGF-2 elicits a repertoire of cellular responses including proliferation, and the protection of cells from programmed cell death or apoptosis. As a result, signalling through the IGF-1R is the principal pathway responsible for somatic growth in foetal mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
470
0
13

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(489 citation statements)
references
References 270 publications
(486 reference statements)
6
470
0
13
Order By: Relevance
“…The insulin-like growth factor 1 receptor (IGF-1R), a tetrameric receptor tyrosine kinase (RTK), is important for transformation, proliferation of malignant cells (Baserga, 1995;Baserga et al, 1997;Adams et al, 2000;LeRoith and Roberts, 2003;Larsson et al, 2005), crucial for preventing apoptosis, maintaining malignant phenotype and for resistance to chemotherapy (Baserga, 1995(Baserga, , 2000Yu and Rohan, 2000;Samani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insulin-like growth factor 1 receptor (IGF-1R), a tetrameric receptor tyrosine kinase (RTK), is important for transformation, proliferation of malignant cells (Baserga, 1995;Baserga et al, 1997;Adams et al, 2000;LeRoith and Roberts, 2003;Larsson et al, 2005), crucial for preventing apoptosis, maintaining malignant phenotype and for resistance to chemotherapy (Baserga, 1995(Baserga, , 2000Yu and Rohan, 2000;Samani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the IGF-1R is overexpressed in multiple cancer types (Xie et al, 1999;Adams et al, 2000;All-Ericsson et al, 2002;Loughran et al, 2005). The elevated expression of IGF-1R in neoplastic cells combined with its crucial roles in malignant growth makes IGF-1R an attractive target in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of IGF-1R in human cancer has raised therapeutic possibilities (Rohlik et al, 1987;Adams et al, 2000;Brodt et al, 2000;Girnita et al, 2000b;Kanter-Lewensohn et al, 2000;Navab et al, 2001; All-Ericsson et al, 2002; Larsson et al, 2005). We recently demonstrated that the cyclolignan PPP specifically inhibits the IGF-1R activity , where it did not inhibit the highly homologous insulin receptor .…”
Section: Introductionmentioning
confidence: 90%
“…The IGF-2R/6-mannose receptor is a monomeric receptor without TK activities. Both IGF-1R and IR are preformed dimeric TK receptors made up by two extracellular a-subunits and two b-subunits involving a small extracellular domain, an intramembraneous one as well as an intracellular domain (Adams et al, 2000). The latter includes the juxtamembraneous domain, the TK domain and the C-terminal domain.…”
Section: Unique Role Of Igf-1r In Cancermentioning
confidence: 99%